Pathogenicity of Malaysian isolates of salmonella enteritidis phage types in specific pathogen-free chickens for vaccine development - Akhtar, Amanullah (2012)
Salmonella enteritidis (SE) is the major and leading cause of food-borne illnesses associated with the consumption of SE contaminated chicken meat, eggs and poultry products. These ever increasing SE outbreaks have leaded the poultry industry and public health agencies to control the SE in commercial poultry. Vaccination against the disease has reduced the SE infection in poultry and subsequently the burden of foodborne illnesses. The objectives of the study were to determine the pathogenicity of Malaysian isolates of SE PTs in specific pathogen-free (SPF) chickens for the development of inactivated vaccine against the disease. The pathogenicity of SE PTs 6A, 7, 3A and 35 was determined in three separate experiments. In experiment 1, one-day-old SPF chicks were divided into sacrificed groups (A1, B1 and C1) of 30 chicks each and mortality groups (MA1, MB1 and MC1) of 20 chicks each. The chicks in groups A1 and MA1 and, B1 and MB1 were inoculated orally with 0.1mL (108cfu/mL) of SE PT6A (UPM-0527) and SE PT7 (UPM-0530), respectively. The non inoculated groups C1 and MC1 served as controls. Clinical signs and mortality were observed twice daily. On days 1, 3, 5, 7, 14 and 21 post inoculations (pi), five chicks were sacrificed from each sacrificed group. Before sacrificed chicks were individually weighed and, cloacal swab and blood samples were collected. On necropsy gross lesions were recorded and samples were collected for bacteriology and histology. The MA1, MB1 and MC1 served to determine the mortality. The same experimental design model was used for experiment 2, where groups A2 and B2 represented the sacrificed groups inoculated with SE PT3A (UPM-0541) and SE PT35 (UPM-0525), respectively. The same experimental design model was also used for experiment 3, except that in this experiment only SE PT6A isolate (UPM-0791) was used, and the chicks were sacrificed as early as 3, 6 and 12 hrs pi and samples were also collected for electron microscopy examination. The clinical signs of depression were 63%, 40%, 40% and 27%, anorexia were 50%, 40%, 30% and 27%, ruffled feathers were 50%, 30%, 40% and 40%, vent pasting were 40%, 37%, 23% and 20% and, diarrhoea were 33%, 20%, 7% and 7% on day 1 pi in SE PT6A (A1), PT7 (B1), SE P3A (A2) and PT35 (B2) inoculated chicks, respectively. Moreover, inability to move was only observed in experiment 1. Diarrhoea was the only clinical sign observed on days 3, 4, 5, 6 and 7pi and intermittently till day 14 pi in experiment 3. Mortality of 20%, 10% and 5% was observed in chicks inoculated with SE PT6A (MA1), SE PT3A (MA2) and SE PT35 (MB2), respectively. The significant (p<0.05) body weight gain difference was recorded in experiment 1. On day one pi, SE isolation was 100% from faecal swab, mid-gut contents, caecal tonsils and caecal contents, 80% from spleen and liver and, 60% from the blood in group A1 (SE PT6A). The PT6A showed highest isolation throughout the experiment followed by PT7, PT3A, PT35 and SE PT6A isolate of ducks. Gross lesions of unabsorbed yolk, airsaculitis, fibrinous pericarditis, fibrinous perihepatitis, enlarged kidneys, splenomegaly were recorded in about 15% of chicks in group A1. Whereas 10% gross lesions were observed in groups B1 (SE PT7), A2 (SE PT3A) and B2 (SE PT35). Mild inflammation was observed in majority of tissues showing lesions. Degeneration and necrosis were observed in spleen, liver and bursa of Fabricius. Electron microscopy showed the Salmonella present in different organs as early as 6 hrs pi. The similar changes as observed in histopathology were noted in electron microscopy. Overall, SE PT6A isolate of chicks was more pathogenic than other PTs studied. The safety and efficacy of inactivated single SE PTs 1, 3A, 6A, 7 and 35 and, their five different combinations were determined in two separate trials. Each SE PT was propagated and fermented individually in the bioreactor at 150rpm, pH 7 and temperature 37°C for 20 hrs. Purity test and plate count was performed. The harvest was collected for single SE PTs and combination of SE PTs, inactivated with 0.7% formaline and kept at 37 °C for 24 hrs. After sterility test adjuvant was added individually in all inactivated single SE PTs and the combinations and, kept for 48-72 hrs. For safety and efficacy, a group of 20 chicks was inoculated subcutaneously with 0.1mL of 1010 cfu/mL inactivated single SE PT or combination being studied. The uninoculated chicks served as controls. Clinical signs and mortality was observed. On day 14pi, 4 chicks from each group were sacrificed after weighing and, collection of blood and cloacal samples. Eight chicks were challenged by orally inoculating with 0.2mL of 1010 cfu/mL of SE PT6A (UPM-0527) on day 14 pi. On days 7 and 14 pc, 4 chicks from each group were sacrificed after weighing and, collection of blood and faecal samples. On necropsy samples were collected for bacteriology and histopathology. In both trials, there was no significant difference (p>0.05) in body weight gain among all the groups. Clinical signs of depression, anorexia and diarrhoea were observed in 10% of chicks in challenged control group (CV0C) on day 3 to 5 post challenged (pc) in the first experiment (single) and almost similar in the second experiment (combination). No post mortem lesions were observed in any of the groups, except that bursa of Fabricius was swollen at 2 weeks pi in the CV0C. On 4 week pi, two serum samples from CV3AC group (inactivated SE PT3A) showed antibody titer of 2407 and 2842. Whereas, from combinations only a serum sample of CV673C group (combination of SE PTs 6A+7+3A) showed antibody titer of 601. The bacteriology results indicated that inactivated SE PTs have the ability to reduced fecal shedding and bacterial isolation from different organs when compared to control challenged chicks. The inactivated single SE PT6A and combination of SE PTs 6A, 3A and 7 were more effective among all the tested PTs. In conclusion, young chicks are more susceptible to SE infections. SE PT6A (A1) is more pathogenic than other PTs studied. The different SE PTs can colonize the intestine and lead to systemic infections on oral inoculation. Different isolates of the same PTs may vary for their pathogenicity. The inactivated single and combination SE PTs are safe and effective to control the disease in chickens. These are able to reduce but are unable to completely eliminate the SE in the host.